Pengaruh Kompres Air Hangat Daerah Aksila Terhadap Perubahan Suhu Tubuh Pada Anak Hipertermia di Ruang Mawar RSUD Kota Kendari - La Ode Liaumin Azim; Ridwan Sulma; Nur Fitriana Muhammad Ali (Jurnal Penelitian Sains dan Kesehatan Avicenna, 2022)
Background: Hyperthermia is an increase body temperature exceeding 38°C due to dysfunction of thermoregulation in the hypothalamus due to problems in the central nervous system. Hyperthermia can cause dehydration, electrolyte imbalance, and seizures if not treated immediately. Hot water compress therapy is one of the therapies to treat fever in children. Objective: To identify the effect of warm compresses on the axillary area on changes in body temperature in hyperthermic children. Methods: Quasi-experimental research design with a pre-test post-test group control approach. The sample of this study were 32 inpatients with hyperthermia in the Rose Room of the Kendari City Hospital from January to June 2022 which were selected by purposive sampling. Data analysis used the Wilcoxon and Mann Whiteney tests. Results: The average decrease in body temperature after the intervention was 1°C in the treatment group, while in the control group it was 0.4°C. The results of the Wilcoxon Signed Rank Test analysis obtained a significance value of p=0.000 in the treatment group, and p=0.000 in the control group, meaning that there was a significant difference in body temperature before and after the intervention. The results of the Mann Whitney U Test statistical test obtained a significance value of p = 0.03, meaning that there was a significant difference in the body temperature of the treatment group and the control group. Conclusion: Warm water compress therapy in the axillary area has an effect on reducing the body temperature of hyperthermic children.